Iron as a sustainable chemical carrier of renewable energy: Analysis of opportunities and challenges for retrofitting coal-fired power plants. (September 2022) - Debiagi, P.; Rocha, R.C.; Scholtissek, A.; Janicka, J.; Hasse, C.
Abstract: As a result of the 2021 United Nations Climate Change Conference (COP26), several countries committed to phasing down coal electricity as soon as possible, deactivating hundreds of power plants in the near future. CO 2 -free electricity can be generated in these plants by retrofitting them for iron combustion. Iron oxides produced during the process can be collected and reduced back to metallic iron using H2, in a circular process where it becomes an energy carrier. Using clean energy in the recycling process enables storage and distribution of excess generated in periods of abundance. This concept uses and scales up existing dry metal cycle technologies, which are the focus of extensive research worldwide. Retrofitting is evaluated here to determine feasibility of adding these material requirements to markets, in the context of current plans for decarbonization of steel industry, and policies on hydrogen and renewable electricity. Results indicate that not only for a single power plant, but also on larger scales, the retrofitting plan is viable, promoting and supporting advancements in sustainable electricity, steel industry and hydrogen production, converging necessary technological and construction efforts. The maturation and first commercial-scale application of iron combustion technology by 2030, together with developing necessary reduction infrastructure over the next decades, would pave the way for large-scale retrofitting and support the phasing out of coal in many regions. The proposed plan represents a feasible solution that takes advantage of existing assets, creates a long-lasting legacy for the industry and establishes circular energy economies that increase local energy security. Highlights: Metals, particularly iron, are very promising as energy carriers. Substitution of coal by iron enables zero-carbon emissions. Transition to clean steel production is possible with green-H 2 . A general formulation for estimating iron requirements is developed. A case study for a single power plant in Germany is presented. The replacement scenario is feasible and can be extended to broader contexts.